2021
DOI: 10.1016/j.bpsc.2020.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Correlates of Beta Bursts in Health and Psychosis: A Concurrent Electroencephalography and Functional Magnetic Resonance Imaging Study

Abstract: Background There is emerging evidence for abnormal beta oscillations in psychosis. Beta oscillations are likely to play a key role in the coordination of sensorimotor information that is crucial to healthy mental function. Growing evidence suggests that beta oscillations typically manifest as transient beta bursts that increase in probability following a motor response, observable as post-movement beta rebound. Evidence indicates that post-movement beta rebound is attenuated in psychosis, with gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…As long as this baseline activity is low, an incoming stimulus would deactivate the spontaneously active network and shift the focus from the internal state to the external environment (1). A recent study (49) demonstrated that sensory-motor beta-bursts correlated with an increase in the task-suppressed hemodynamic signal in the sensory-motor network. A near-threshold stimulus was given upon detection of exactly 0 (quiet), 150 (low), 300 (medium), or more than 400 (high) burst samples during the detection window and the 600 ms preceding it.…”
Section: Discussionmentioning
confidence: 99%
“…As long as this baseline activity is low, an incoming stimulus would deactivate the spontaneously active network and shift the focus from the internal state to the external environment (1). A recent study (49) demonstrated that sensory-motor beta-bursts correlated with an increase in the task-suppressed hemodynamic signal in the sensory-motor network. A near-threshold stimulus was given upon detection of exactly 0 (quiet), 150 (low), 300 (medium), or more than 400 (high) burst samples during the detection window and the 600 ms preceding it.…”
Section: Discussionmentioning
confidence: 99%
“…Although PMBR is usually quantified by averaging the beta power across a time window following movement, observation of data acquired in single trials reveals that the smooth peak of beta activity observed in trial averaged data actually represents the superposition of transient bursts of beta activity with duration of order 150 ms occurring with increased probability in the PMBR time window. In a study employing concurrent EEG and fMRI to assess brain activity during the n-back working memory task, Briley et al (2021) confirmed that beta-burst rate following button press responses was diminished in schizophrenia, and also in psychotic bipolar disorder, compared with healthy controls. The reduction was less marked in the bipolar cases.…”
Section: Evidence For Excessively Imprecise Predictionsmentioning
confidence: 83%
“…So far there is limited evidence that assessment of the relevant symptoms and cognitive measures are sufficiently sensitive and reliable to provide clinically useful estimates of prognosis in an individual case. However, the evidence that classical features are correlated with electrophysiological features such as inter-trial coherence during target detection tasks ( Doege et al, 2010 ) and beta-bursts related to movement ( Rathnaiah et al, 2020 ; Briley et al, 2021 ; Gascoyne et al, 2021 ) indicates a practical approach to enhancing prediction. It is practical to measure these electrophysiological features in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies that used resting-state conditions in SCZ found that beta power was positively correlated (decreased in EEG activity—worse cognitive performance) with different cognitive functions, such as emotion recognition [ 85 ], vigilance, working memory, visual and verbal memory [ 109 ]. Furthermore, two studies investigating task-related activity reported a positive association of evoked beta bursts [ 114 ] and evoked beta activity [ 99 ] with working memory. However, also a lack of associations between beta power and verbal learning [ 86 ], working memory [ 86 ] and metacognitive functions [ 122 ] has been reported.…”
Section: Resultsmentioning
confidence: 99%